Why AI in Medical Imaging Relies on GPUs Over CPUs - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Explore why GPUs outperform CPUs in AI training for medical imaging, enabling faster and more efficient diagnostic model development.
Keywords: GPU; CPU; AI in Healthcare; Medical Imaging; Deep Learning; Abdominal Aortic Aneurysm; Digital Health